Wood‐Derived Hierarchically Porous Electrodes for High‐Performance All‐Solid‐State Supercapacitors. (9th November 2018) - Wang, Yameng; Lin, Xiangjun; Liu, Ting; Chen, Heng; Chen, Shuai; Jiang, Zhongjie; Liu, Jiang; Huang, Jianlin; Liu, Meilin
Abstract: The rapid development of many emerging technologies (e.g., electric vehicles and smart grids) requires advanced energy storage and conversion systems that have higher energy and power density, longer operational life, and better safety. A low‐cost, green, and sustainable process for fabrication of all‐solid‐state asymmetric supercapacitors (ASC) composed of a hierarchically porous carbonized wood (CW) anode, a cellulose paper separator, and a Co(OH)2 @CW cathode is reported here. The hierarchically porous wood‐derived electrode exhibits a high areal capacitance of 3.723 F cm −2 (with an areal loading Co(OH)2 of 5.7 mg cm −2 ) at a current density 1.0 mA cm −2, and 1.568 F cm −2 at a current density of 30 mA cm −2 . Moreover, the all‐solid‐state ASC exhibits outstanding energy density of 0.69 mWh cm −2 (10.87 Wh kg −1 ) at power density of 1.126 W cm −2 (17.75 W kg −1 ) while maintaining a capacitance retention of 85% after 10 000 continuous charge–discharge cycles. The high energy/power‐densities are attributed to the unique architecture of the electrodes derived from natural wood, which allow full exposure of active electrode materials, efficient current collection, and fast ion transport. Further, the materials are renewable, environmentally friendly, and biodegradable. Abstract : A high‐performance wood‐derived composite electrode enables excellent capacity, rate capability, and cycle stability of an all‐solid‐state asymmetric supercapacitor. The electrode is composed of hierarchically porous while structurally continuous Co(OH)2 nanoflakes tightly bonded on the surfaces of the carbonized wood and inside its multichannels.